Periodization training for sport - Bompa, T.; Buzzichelli, C. A. (Human Kinetics, 2015)
Sport conditioning has advanced tremendously since the era when a "no pain, no gain" philosophy guided the training regimens of athletes. Dr. Tudor Bompa pioneered most of these breakthroughs, proving long ago that it's not only how much and how hard an athlete works but also when and what work is done that determine an athlete's conditioning level. Periodization Training for Sports goes beyond the simple application of bodybuilding or powerlifting programs to build strength in athletes.